Research on the Origin and Value Analysis of Kaiping Diaolou, a World Cultural Heritage Site - Zhang, Wansheng; Sharul Azim Bin Sharudin (International Journal of Social Sciences and Public Administration, 2024)
This study aims to explore the origins and cultural value of Kaiping Diaolou, a UNESCO World Cultural Heritage site. By combining literature analysis with field investigations, the research delves deeply into the historical background and architectural characteristics of the Diaolou. The findings reveal that Kaiping Diaolou integrates both Chinese and Western architectural styles, reflecting the unique regional culture and the historical significance of ethnic fusion. Kaiping Diaolou is not only a symbol of overseas Chinese culture but also a model of Sino-Western cultural integration, embodying rich historical connotations and profound social significance. This study provides a critical basis for the preservation and inheritance of this heritage. Moreover, the defensive function of the Diaolou, along with its social symbolic meaning within the local community, further highlights its important status in global cultural heritage.